Práticas pedagógicas de uma professora de educação física de início de carreira: um estudo de caso - Costa, Catia Silvana da (Universidade Federal de São Carlos, 2013)
Early career, presented by its complexity, is still in a little explored topic in the world of teacher education. Given the importance of conducting research on the period and the interest in the implementation of actions directed to the initial and continuing training and start teaching, we intend, in this study, know and understand the pedagogical practices of a novice teacher of Physical Education and sources that influence the construction of knowledge in the course of his career. Based on this goal, we reflect on the teacher beginner, the characteristics and implications of this period, initial training in Physical Education, the dimensions of the processes of learning and professional development and teacher knowledge. Similarly, we contextualize Physical Education resuming its historical trajectory to provide visibility and understanding of the constitution of the area, we situate the various trends, we present the construction of the concept of body culture, based our education on a full-length, legislation for Physical Education and studies on the teaching of physical education in the early years of elementary school. Subsidized by qualitative research, we developed a case study with a Physical Education teacher in her fourth year of professional experience in the early years in two schools in the school system of the State Secretary of Education of São Paulo (SSE-SP) in Bauru. We conducted observations, interviews, analyzing documents, we characterize the teacher, contextualize schools and present how the analysis axes were constructed. Based on analyzes of the axes "school subject", "nature of practices: organization, reasoning and evaluation", "teachers dilemmas" and "challenges of physical education in school interventions, relationships and perspectives", consider the participant, not as a beginner teacher, but as a teacher of early career by moving between developing practices successful and some conflicts commonly experienced in the period from entry into teaching, evidence that generally are not defined by the literature on the subject. Such practices are based on a contextualized and interdisciplinary teaching perspective, redefines student learning beyond the procedures. The dialogue with the literature, exchanges with peers, courses and previous experiences reveal the intentionality of the actions of participants and their commitment to the students and the training itself. As a result, their practices relate to the characteristics of a good teacher and an experienced teacher and confirmed the need for public policies to understand the teacher as builder and transmitter of knowledge, to take ownership of this knowledge to propose actions to facilitate training and optimize the process of learning and professional development, helping to ease the hardships of his early career. Also, we intuit that this study may contribute to the early reflections essential to systematize guidelines for public policies for initial and continuing training of physical education teachers who work and who will act in the early years of elementary education in the schools of SSE-SP, and concomitantly promote new dialogues on pedagogical practices of teachers of Physical Education beginners.
Keywords: Professores; Formação inicial; Aprendizagem; Desenvolvimento profissional; Saberes docentes; Educação física; Professora de educação física de início de carreira; Formação inicial e continuada; Anos iniciais do ensino fundamental; Physical education teacher of early career; Initial and continuing training; Years of primary school; CIENCIAS HUMANAS::EDUCACAO